Analysis of major liver injuries requiring laparotomy in children: Bile peritonitis and the factor of ligamentum falciforme - Kazez, Ahmet; Özel, Şeyhmus Kerem; Bakal, Ünal (My University, 2007)
Aim: Nonoperative conservative approach is the recommended form of management of the pediatric intraabdominal solid organ injuries. To identify the possible impact of ligamentum falciforme in intraabdominal solid organ injuries, a retrospective analysis of the records of patients with liver laceration who underwent laparotomy while being followed conservatively in our clinics after blunt abdominal trauma was performed. Material and Methods: Thirteen patients with liver laceration due to trauma who were treated with laparotomy between 1999 and 2005 were included in the study. Three patients with liver trauma who died due to causes other than liver injury and those treated conservatively were excluded. Patients who had bleeding or bile peritonitis were divided into two groups. Serum bilirubin and transaminase levels of the groups were evaluated. The statistical analysis was done with Mann-Whitney U test. Results: The cause of trauma was fall in 1 patient, occupant of car accidents in 2 and pedestrians in 10 patients. In 7 out of the patients, the injury was close to the dome of right lobe and all of them were operated at the first day of trauma (Bleeding Group). In this group, the mean total bilirubin level was 0.77±0.09 mg/dl and liver enzymes (AST/ALT) were 772±396/ 608±266 U/L. Six patients required operation due to bile peritonitis during being followed conservatively (Bile Group). The mean timing of operation was 3 days (2-5 days) after trauma in this group. The mean total bilirubin level was 3.51±2 mg/dl and liver enzymes (AST/ALT) were 1019±717/ 723±369 U/L. Lacerations were detected at the right lobe posterior-lateral margin in 1 patient and the interlobar fissure of ligamentum falciforme in 5 patients (right side in 4, left side in 1). The increase in bilirubin levels was statistically significant in bile croup in comparison with bleeding group (p=0.001). Conclusion: Bile leakage should be considered in cases with lacerations near ligamentum falciforme during conservative follow-up of liver injuries. Laparotomy may be indicated in case of increased abdominal tenderness and bilirubin levels. Ligamentum falciforme may be the cause of parenchymal laceration in acceleration/deceleration type trauma while it actually protects the liver from major vascular injuries.
Laparatomi uygulanan karaci?er yaralanmalarinin analizi: Safra peritoniti ve ligamentum falsiforme faktörü
Keywords: Bile peritonitis; Child; Ligamentum falciforme; Liver injury; Trauma